Competency in police administration: A study of two police units in Andhra Pradesh - Sudarshanam, G.; Pradeep, N. Chaitanya (2015)
In public administration literature, an increasing attention has recently been paid to the concept of competency. There seems to be a growing consensus among writers on administration that in many government organisations, issues of human resource are the most critical of all resources. Competence constitutes critical resource in the context of police organisation's capability to meet the challenges and stay effective. Besides being a central resource in itself, for productive utilisation of human resource police management needs to keep the subordinate police officers' competency high. In other words, competency is a necessary condition for effective policing. It helps the police organisation to meet the challenges that have surfaced due to the globalisation and technological interventions. The purpose of this article is to understand how the competency of the police personnel is being influenced by the managerial factors. However, this perspective is different from traditional ways of viewing competence in the strategic management and organisational theory literature. The article argues that competency in police organisation is not only determined by the quality and composition of human and material resources per se, but also by the way in which they are being managed with requisite motivation.- Reproduced.
Keywords: Police - India - Andhra Pradesh; Police